PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS MELALUI PEMBELAJARAN ACCELERATED LEARNING - R H Yanti Silitonga (Program Studi Pendidikan Matematika, 2019)
This research aims to determine enhancing students mathematical problem solving through the implementation of accelerated learning. This study is a quasi experiment with control group pretest-postest design. The study had been conducted with 66 students of SMP in Bandung. The experiment group obtained accelerated learning and control group obtained expository learning. Data was collected from students trough mathematical problem solving test. Data was analyzed using average of difference test that was Mann-Whitney and showed that the enhancement of mathematical problem solving ability of students who have obtained accelerated learning are better than students who have obtained expository learning.